Determinasi Faktor Lingkungan Mikro Terhadap Sebaran Kasus Tuberkulosis Paru di Kota Dumai: Studi cross-sectional - Surya Hajar Fitria Dana; Susanti Dwi Ariani; Syaiful Ramadhan Harahap (SEHATI: Jurnal Kesehatan, 2024)
Mycobacterium tuberculosis is the second leading cause of death worldwide, after COVID-19. This study investigated the prevalence and microenvironmental determinants of pulmonary TB in Dumai City, focusing on the urban areas. Using a cross-sectional approach in three areas with high, medium, and low rates of pulmonary TB, this study identified the ventilation, lighting, humidity, floor and wall material type, and occupancy density variables that influence pulmonary TB transmission. The results showed that inadequate microenvironmental conditions significantly contributed to the spread of pulmonary TB. Effective management of these microenvironmental risk factors is essential as a basis for public health interventions to reduce the TB prevalence in Dumai City.